Eksodus Etnis Tionghoa dari Kudus ke Semarang Akibat Konflik antaretnis di Kudus 1918 - Moh Abdul Rochim; Ufi Saraswati (Universitas Hamzanwadi, 2026)
This study examines the inter-ethnic conflict in Kudus in 1918, which led to the exodus of ethnic Chinese to Semarang. The research focuses on the factors causing the conflict, the dynamics of the riots, and the socio-economic implications of the migration. The research employs historical methods through heuristics, source criticism, interpretation, and historiography. Primary sources include contemporary newspapers such as De Preanger Bode, De Indier, De Locomotief, Dagblad van Zuid Holland en ’s Gravenhage, and Het Nieuws van den Dag voor Nederlandsch-Indie, supported by secondary sources from scholarly literature. The results indicate that the conflict was not caused by a single factor, but by the accumulation of socio-economic tensions, social segregation, and sensitivities over ethnic and religious identities. Competition in strategic economic sectors such as the kretek (cigarette) industry and trade intensified intergroup prejudice, which was then fueled by symbolic incidents in the public sphere. The riots that occurred on October 31, 1918, caused extensive damage, loss of life, and insecurity, prompting much of the Chinese community to leave Kudus. The exodus to Semarang is understood as a rational strategy to secure security and restore socio-economic life through stronger community networks. This movement also demonstrates that migration in conflict situations is a form of structured social adaptation. Thus, this study confirms that communal conflict not only results in physical violence but also drives demographic, social, and economic changes with long-term impacts.